Analisis Miskonsepsi Siswa terhadap Bilangan Berpangkat - Anisa Anisa; Khoirun Nisak (Student Research Journal, 2023)
Some previous research results indicate the existence of misconceptions experienced by students in solving exponential number problems. This study aims to analyze the forms of misconceptions frequently made by students in solving exponential number problems. The research design used in this study is qualitative research, aiming to gain a deep understanding of the forms of misconceptions experienced by students in solving problems related to exponential numbers. The research was conducted at one of the private Islamic junior high schools in the Grati District, with 32 students as the data source, focusing only on 6 specific students: 2 high-ability students (subject 1), 2 medium-ability students (subject 2), and 2 low-ability students (subject 3), selected directly by the mathematics teacher in the class. The research instrument in this study was in the form of a test.